The endocannabinoid 2-arachidonoylglycerol promotes endoplasmic reticulum stress in placental cells. Issue 2 (August 2020) - Almada, Marta; Costa, Lia; Fonseca, Bruno; Alves, Patrícia; Braga, Jorge; Gonçalves, Daniela; Teixeira, Natércia; Correia-da-Silva, Georgina
Abstract : Proliferation, differentiation and apoptosis of trophoblast cells are required for normal placental development. Impairment of those processes may lead to pregnancy-related diseases. Disruption of endoplasmic reticulum (ER) homeostasis has been associated with several reproductive pathologies including recurrent pregnancy loss and preeclampsia. In the unfolded protein response (UPR), specific ER-stress signalling pathways are activated to restore ER homeostasis, but if the adaptive response fails, apoptosis is triggered. Protein kinase RNA-like endoplasmic reticulum kinase (PERK), inositol-requiring enzyme 1 (IRE1) and Activating transcription factor 6 (ATF6) are central players in UPR and in ER-stress-induced apoptosis, as well as downstream transcription factors, as C/EBP homologous protein (CHOP). Our previous studies have shown that the endocannabinoid 2-arachidonoylglycerol (2-AG) modulates trophoblast cell turnover. Nevertheless, the role of ER-stress on 2-AG induced apoptosis and cannabinoid signalling in trophoblast has never been addressed. In this work, we used BeWo cells and human primary cytotrophoblasts isolated from term-placenta. The expression of ER-stress markers was analysed by qRT-PCR and Western blotting. ROS generation was assessed by fluorometric methods, while apoptosis was detected by the evaluation of caspase -3/-7 activities and Poly (ADP-ribose) polymerase (PARP) cleavage. Our findings indicate that 2-AG is able to induce ER-stress and apoptosis. Moreover, the eukaryotic initiation factor 2 (eIF2α)/CHOP pathway involved in ER-stress-induced apoptosis is triggered through a mechanism dependent on cannabinoid receptor CB2 activation. The results bring novel insights on the importance of ER-stress and cannabinoid signalling on 2-AG mechanisms of action in placenta.